Investigation of the Role of Genes Encoding Zinc Exporters zntA, zitB, and fieF during Salmonella Typhimurium Infection - Huang, Kaisong; Wang, Dan; Frederiksen, Rikki F.; Rensing, Christopher; Olsen, John E.; Fresno, Ana H. (Frontiers in Microbiology, 2018)
The transition metal zinc is involved in crucial biological processes in all living organisms and is essential for survival of Salmonella in the host. However, little is known about the role of genes encoding zinc efflux transporters during Salmonella infection. In this study, we constructed deletion mutants for genes encoding zinc exporters (zntA, zitB and fieF) in the wild type (WT) strain S. Typhimurium 4/74. The mutants 4/74ΔzntA and 4/74ΔzntA/zitB exhibited a dramatic growth delay and abrogated growth ability, respectively, in LB medium supplemented with 0.25 mM ZnCl2 or 1.5 mM CuSO4 compared to the WT strain. In order to investigate the role of genes encoding zinc exporters on survival of S. Typhimurium inside cells, amoeba and macrophage infection models were used. No significant differences in uptake or survival were detected for any of the mutants compared to the WT during infection of amoebae. In Nramp1-negative J774.1 murine macrophages, significantly higher bacterial counts were observed for the mutant strains 4/74ΔzntA and 4/74ΔzntA/zitB compared to the WT at 4 hours post infection although the fold net replication was similar between all the strains. All four tested mutants (4/74ΔzntA, 4/74ΔzitB, 4/74ΔfieF and 4/74ΔzntA/zitB) showed enhanced intracellular survival capacity within the modified Nramp1-positive murine RAW264.7 macrophages at 20 hours post infection. The fold net replication was also significantly higher for 4/74ΔzntA, 4/74ΔzitB and 4/74ΔzntA/zitB mutants compared to the WT. Intriguingly, the ability to survive and cause infection was significantly impaired in all the three mutants tested (4/74ΔzntA, 4/74ΔzitB and 4/74ΔzntA/zitB) in C3H/HeN mice, particularly the double mutant 4/74ΔzntA/zitB was severely attenuated compared to the WT in all the three organs analysed. These findings suggest that these genes encoding zinc exporters, especially zntA, contribute to the resistance of S. Typhimurium to zinc and copper stresses during infection.